PENGARUH PEMBERIAN JUS BUAH PEPAYA UNTUK PRODUKSI ASI PADA IBU MENYUSUI DI TPMB NY. S DI DESA BULUNGANYAR KECAMATAN LEKOK PASURUAN - Mauludiah, Putri; Widiatril, Raden Maria Veronika; Sulistiyah, Sulistiyah (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
Exclusive breast milk based on Government Regulation Number 33 of 2012 is breast milk given to babies from birth for six months, without adding or replacing it with other food or drinks (except medicines, vitamins and minerals). The regulation of exclusive breastfeeding aims to guarantee the fulfillment of the baby's right to exclusive breastfeeding from birth to six months of age by paying attention to growth and development, providing protection to mothers in providing exclusive breastfeeding to their babies and increasing the role and support of the family, community, regional government and the government. towards exclusive breastfeeding (Ministry of Health of the Republic of Indonesia, 2018). This study aims to determine the effect of giving processed papaya fruit juice to facilitate breast milk production for breastfeeding mothers in TPMB Ny S Lekok Pasuruan. The type of research used is pre-experimental, the method used is quantitative with a quasi-experimental design, pretest and posttest group approach. The population in this research is postpartum mothers on days 3 to 7 based on data obtained from the month of August to October 2023. Mothers obtained 20 people gave birth with exclusive breast milk. The analysis used the Wilcoxon paired test. The results of the Wilcoxon paried test show that (p=0.000), meaning there is an effect of giving processed papaya fruit juice to increase breast milk production for breastfeeding mothers. Giving processed papaya fruit juice can increase breast milk production for nursing mothers.